RESULTS OF THE 4YEAR PROSPECTIVE OBSERVATION IN THE PROSPECTIVE TRIAL INTEREPID: FACTORS INFLUENCING MORBIDITY AND MORTALITY IN THE POPULATION OF RURAL REGIONS OF RUSSIA AND KYRGYZ REPUBLIC - A. V. Kontsevaya; A. О. Myrzamatova; A. N. Khalmatov; M. B. Khydyakov; A. G. Polupanov; A. Т. Altymysheva; Yu. А. Balanova; А. К. Kashirin (Кардиоваскулярная терапия и профилактика, 2018)
Recent decades, cardiovascular diseases (CVD) remain the leading cause of mortality throughout the world. The prevalence of the main risk factors (RF) for CVD varies ethnically and geographically. Single observations witness that native and nonnative populations inhabiting various, often quite contrast climatic and geographical, as socialeconomic conditions, might show a broad variety in CVD and RF prevalence.Aim. To evaluate the 4year survival rate in association with the RF and cardiovascular morbidity and mortality among rural inhabitants of Russia and Kyrgyz Republic, with analysis of ethnic specifics (by the data from trial “Interepid”).Material and methods. The study was conducted under the framework of international project “Interepid” that included momentary epidemiological study of the prevalence of the main chronic noncommunicable diseases and RF, and prospective step in small town and rural settlements of two countries — Russia and Kyrgyz Republic. In the analysis the results included of representative selections of rural inhabitants of the Volzhskiy region of Samarskaya Oblast of Russia (n=1050), and of Chuyskaya Oblast of Kyrgyz Republic (n=1341), age 2064 y. o. In Russia and in Kyrgyz Republic the study was done by one protocol Interepid with specifically developed surveys (20112012). To the analysis, the endpoints included: allcause mortality, CVD mortality, nonfatal cardiovascular events: nonfatal myocardial infarction, nonfatal stroke or transient ischemia, unstable angina, revascularization of any vascular pool — coronary bypass, endovascular revascularization, carotid endarterectomy, lower limbs arteries revascularization.Results. The standardised by age survival rate was higher among the Kyrgyz Republic inhabitants — 98,8%, and in Samarskaya oblast — 95,7%. In Kyrgyz Republic the fatal and nonfatal cardiovascular endpoints were registered in 14,7% responders, with no ethnical differences, and in Samarskaya oblast — only in 2,1% (p<0,01). Smoking had significant influence on adverse outcomes only in males in both selections. The influence of arterial hypertension was nonsignificant for the outcomes in Samarskaya Oblast during 4year observation, however there was significant influence of this RF in Kyrgyz Republic. Overconsumption of animal fat among the Kyrgyz Republic inhabitants associated with the development of nonfatal cardiovascular outcomes, with no ethnical differences.Conclusion. The comparison of the results in three groups of population showed different impact of RF on development of the analyzed adverse outcomes in 4 years of prospective followup. Regardless the not that long term followup, the data obtained at the moment witness on reliable and prognostically significantly adverse influence of smoking, arterial hypertension and overconsumption of animal fat on the development of analyzed outcomes among the studied populations with ethnical and local differences. All these point the necessity is clear for development of differential management programs and events in Russian population and in native inhabitants of Kyrgyz Republic, including the specifics of CVD RF prevalence and influence on life prognosis.